TEVAR, multilayer stents and CERAB procedure for complicated type B aortic dissection: a case report - Andreea Costache; Jorn P. Meekel; Anca Chitic; Silviu L. Dumitrescu; Radu Popa; Kak K. Yeung; Victor S. Costache (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Background: In case conservative medical treatment fails or symptoms persist in type B thoracic aortic dissection (TBAD), invasive treatment with thoracic endovascular repair (TEVAR) is recommended. TEVAR aims to prevent aneurysm formation, reduce rupture risk, and improve survival rates if initiated early. However, TEVAR may not always sufficiently remodel the aorta, especially when there are existing tears further down. Some studies suggest extending the stent graft with bare metal stents to enhance aortic remodeling, but the PETTICOAT technique can be complex with incomplete clotting and aortic dilation. This case report introduces the Multilayer Flow Modulator stent (MFM®) as a novel technique that combines stent graft and bare metal stenting advantages while avoiding PETTICOAT limitations. Case report: A 47-year-old male with a history of hypercholesterolemia, smoking, and obesity presented with lower back pain and claudication. A diagnostic CT scan revealed type TBAD with tears at various levels. Initial treatment involved antihypertensive therapy, but the patient later experienced worsened symptoms. A two-stage intervention was performed, utilizing multilayer stents and a Valiant thoracic stent graft to cover the dissected areas. The patient had a successful recovery with improved aortic lining and maintained kidney function. Follow-up scans showed stable aortic diameter and no further complications. Conclusion: This case report presents a successful treatment of a complicated TBAD using a combination of stent grafts and multilayer aortic stents. Follow-up after one year showed significant improvement in aortic remodeling, with thrombosis of the false lumen and patent aortic branches. The patient became asymptomatic with no claudication or thoracic pain. The combined approach appears to be a safe and effective treatment option, but more research is necessary for validation.